The effect of cocoa, soy, oats and fish oil on metabolic syndrome in rats - Barrios-Ramos, Juan P.; Garduño-Siciliano, Leticia; Loredo Mendoza, María Lilia; Chamorro-Cevallos, German; Jaramillo-Flores, Maria E. (My University, 2012)
Background: The effect of functional foods alone or in combination (cocoa + soy + oats + fish oil) on hepatic damage in rats affected with metabolic syndrome was investigated. Results: Rats that were given cocoa showed a decrease in the levels of triglycerides (TGs) and glucose (63 and 32% respectively) as well as a decrease in blood pressure (15%). Animals fed with soy showed a reduction of 21% in total cholesterol, 15% in blood pressure and 44% in TGs, while feeding oats reduced the concentration of TGs by 53% (P < 0.5). Fish oil caused a reduction in TGs (56%) and glucose (26%). The effect on blood pressure was statistically significant for the groups supplemented with cocoa, soy, cocoa + oats and the total mix. The main finding was a reduction in liver steatosis in animals supplemented with cocoa + oats (from 30 to 4.7% steatosis). Cocoa or fish oil alone did not protect the liver from damage, while cocoa + fish oil did.